Ceza hukukunda hukuka uygunluk nedenlerinin manevi unsurları meselesi - Dursun, Selman; Bozbayındır, Ali Emrah (İstanbul Üniversitesi Hukuk Fakültesi, 2015)
Unknown justification is one of the most contested themes in criminal law dogmatic and there is a wide range of views on this issue. According to the objective conception of justifications there is no place for a "subjective" intent and/or knowledge element, which is still the prevailing view in the Turkish Criminal Law. Yet, with the introduction of the new Penal Code there is a newly, under the German influence emerging theory of subjective elements of justification, makes the existence of a subjective element a necessary component for justifying reasons for otherwise criminal conduct. There exists, however, a lack of clarity concerning the legal consequences of this new theory. It is the objective of this article to sum up views, historical background and try to resolve this newly emerging issue in Turkish Criminal Law.
The problem of unknown justification in criminal law
WOS: 000409893400003
Keywords: Unlawfulness; personal injustice theory; justifications; material elements; mental elements; impossible attempt; impossible crime; mistake; reversed mistake; Hukuka aykırılık; Şahsi haksızlık öğretisi; Hukuka uygunluk nedenleri; Maddi unsurlar; Manevi unsurlar; Elverişsiz teşebbüs; Mefruz suç; Hata; Tersine hata